2017
DOI: 10.1002/pros.23463
|View full text |Cite
|
Sign up to set email alerts
|

Capillarisin blocks prostate‐specific antigen expression on activation of androgen receptor in prostate carcinoma cells

Abstract: Our results indicated that Cap inhibited growth of LNCaP cells. Cap effectively suppressed androgen activation on AR-mediated transactivation, which is AR-dependent through AR degradation and dissociation of AR-Hsp90 in prostate carcinoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
(68 reference statements)
2
14
0
Order By: Relevance
“…These results were consistent with other studies in human breast carcinoma cells, MCF7, osteosarcoma and B‐lymphoblast cells, although some of them showed cell apoptosis was induced with higher Cap concentrations . The EC50 between DU145 and LNCaP after Cap treatments for 48 and 72 hours has shown no significant differences; however, recent study revealed that Cap blocks androgen activation on AR‐mediated prostate specific antigen expression in LNCaP cells . Whether Cap has the same effect on prostate normal epithelial cells still needs further investigations.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These results were consistent with other studies in human breast carcinoma cells, MCF7, osteosarcoma and B‐lymphoblast cells, although some of them showed cell apoptosis was induced with higher Cap concentrations . The EC50 between DU145 and LNCaP after Cap treatments for 48 and 72 hours has shown no significant differences; however, recent study revealed that Cap blocks androgen activation on AR‐mediated prostate specific antigen expression in LNCaP cells . Whether Cap has the same effect on prostate normal epithelial cells still needs further investigations.…”
Section: Discussionsupporting
confidence: 89%
“…Prostate cancer is one of the most frequently diagnosed malignancies and the leading cause of cancer‐related deaths in men worldwide . In this study, we demonstrated that Cap suppressed cell growth without inducing apoptosis in androgen‐independent DU145 cells since the Cap did not significantly induce poly (ADP‐ribose) polymerase (PARP) cleavage form, an apoptotic marker, which is similar to a previous study in androgen‐dependent LNCaP cells . Moreover, the Cap‐inhibited cell growth of prostate carcinoma cells was due to its induction of cell cycle arrest at the G0/G1 phase (Figures and ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations